MENGGALI NILAI-NILAI KEBANGSAAN DALAM PANCASILA SEBAGAI GROUNDNORM NEGARA KESATUAN REPUBLIK INDONESIA - Mahardika, Ahmad Gelora (Ahkam: Jurnal Hukum Islam, 2018)
The states value is based on the norm in the state of life. Pancasila (five principles) as the supreme legacy of the founding fathers is a groundnorm which is equal to life, liberty and the pursuit of the happiness which was created by USA founders or liberty, and is equal to egality and fraternity which  was created by France philosophers. But, years after years, regime to regime, Pancasila becomes more difficult to be understood. Even, Pancasila often becomes the tools for the status quo to run his authority. Pancasila as an abstract norm, can only be interpreted by the authority. By watching and observing the office of government, the writer hopes to find the states value hidden in the Pancasila.Keywords: Values, states, Pancasila, authority